Real Exchange Rates In Developing Countries : Are Balassa-Samuelson Effects Present? - Khan, Mohsin (IMF Working Papers; Working Paper, 2004)
There is little empirical research on whether Balassa-Samuelson effects can explain the long-run behavior of real exchange rates in developing countries. This paper presents new evidence on this issue based on a panel data sample of 16 developing countries. The paper finds that the traded-nontraded productivity differential is a significant determinant of the relative price of nontraded goods, and the relative price in turn exerts a significant effect on the real exchange rate. The terms of trade also influence the real exchange rate. These results provide strong verification of Balassa-Samuelson effects for developing countries.